The Influence Of Bank Health Ratio On Profitability In PT. Bank SULSELBAR Makassar, Indonesia - Auliyah Nurwafiyyah; Fadlina; Mariam Makmur (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
The objective of this research is to analyse the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operations Expenses to Operation Income (BOPO) toward Return On Equity (ROE). Secondary data were obtained from quarterly report of PT. Bank Sulselbar Makassar covering the period of 2010 until 2017. F test shows that in simultant variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operations Expenses to Operation Income (BOPO), influence Return On Equity (ROE). While, partially with t test show that CAR and LDR variables show positive and doesn’t have significant to ROE, NPL variable show negative and significant to ROE, and BOPO variable show negative and doesn’t have significant to ROE. Predictive ability of the four independent variabels to ROE is 42,6% and it shown by adjusted R2 value, the rest 57,4% influenced by other variabel outside the model.